Advances in hydroscience. - Chow, Ven Te, 1919-1981 (Academic Press, 1971)
Advances in Hydroscience, Volume 7 covers topics on the progress in the field of hydroscience. The book presents articles on the theoretical characteristics of water gravity waves generated by explosions; the dynamics of glaciers, including progress in field techniques and ice rheology; and the dispersion in porous media. The text also includes articles on seepage through dams, as well as the concept of hydrobionics and the examples of biological flows which can lead to useful engineering applications. Oceanic engineers, coastal engineers, hydrologists, hydraulicians, hydraulic engineers, an.